Beyond Classroom Time: Evaluating Mastery Based Learning and Competency Achievement in Secondary Schools - Wijaya Wijaya; Noerfannyda Noerfannyda; Kelepi Nalatu (PT. Sinergi Bersahaja Sejahtera, 2026)
Background. Competency-Based Education (CBE) emphasizes demonstrated mastery rather than learning duration as the basis for student progress. However, the continued dominance of seat-time-oriented practices raises questions about how effectively CBE principles are being implemented in secondary schools.. Purpose. This study aims to examine the relationship between mastery-based learning, classroom learning time orientation, competency achievement, and perceptions of learning effectiveness among secondary school students. Method. A cross-sectional quantitative survey was conducted with 310 high school students in Palembang, Indonesia, selected through random sampling. Data were collected using a structured questionnaire and analyzed using descriptive statistics, Pearson correlation, and regression analysis. Novelty. This study offers a multidimensional assessment of CBE by positioning mastery-based learning and seat-time orientation as contrasting predictors of students’ competency achievement and perceived learning effectiveness. Results. Mastery-based learning was positively associated with perceived learning effectiveness (r = .610, p < .001) and significantly predicted competency achievement (? = .454, p < .001). In contrast, seat-time orientation showed a significant negative association with competency achievement (? = -.157, p = .002). Conclusion. The findings support a shift toward mastery-governed learning in which demonstrated competency becomes the primary basis for academic progression, while instructional time functions as a flexible resource for achieving mastery.